Motif Penggunaan Gadget Sebagai Sarana Promosi Bisnis Online di Kalangan Mahasiswa UIN Sunan Kalijaga - Nurul Izzati (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2015)
The presence of gadgets mainly in the form of smartphones has much to contribute in everyday life, as a media gadget information search, interacting, get entertained, even for the purpose of online business activities for today is widely used among students of UIN Sunan Kalijaga. This study aimed to describe the motives of use gadgets as online business promotion tool among students UIN Sunan Kalijaga. The research approach uses qualitative approach with descriptive qualitative method, focus of research is the use of gadgets motivation among students. Respondent with purposive sampling. The research found patterns of use gadgets as a means of business promotion online, such as, First, the use of gadgets are considered more convenient, easy and simple to do promotions, Second, Online Business is suitable for small businesses run by selling a variety of products. Third, Doing business online using a gadget or self-awareness initiative of informants in sufficient portion of the needs as well as training yourself to be an independent figure.